Chemerin Expression in the Peritoneal Fluid, Serum, and Ovarian Endometrioma of Women with Endometriosis. (9th June 2015) - Jin, Chan Hee; Yi, Kyong Wook; Ha, Young Ran; Shin, Jung‐Ho; Park, Hyun Tae; Kim, Tak; Hur, Jun‐Young
Abstract : Problem: Inflammation is an essential process in the pathogenesis of endometriosis. Method of study: Serum and peritoneal fluid (PF) samples were collected from women with endometriosis ( n  = 31) and women without endometriosis ( n  = 48). Chemerin, tumor necrosis factor‐alpha (TNF‐α), and interleukin‐6 (IL‐6) levels in serum and PF samples were determined with a specific enzyme‐linked immunosorbent assay. Eutopic endometrial tissue from controls and ovarian endometriotic cysts were obtained during surgery. Expression of chemerin and chemerin receptors in ectopic and eutopic endometrial tissues was measured on real‐time reverse transcriptase–polymerase chain reaction. Protein expression was examined with Western blot and densitometric analysis. Results: Chemerin concentrations were higher in PF from women with endometriosis than that in that from controls. PF chemerin concentrations were significantly correlated with both TNF‐α and IL‐6 levels in PF. The mRNA and protein of chemerin and its receptor were significantly increased in the ovarian endometrioma tissue compared with eutopic endometrium of controls. Conclusion: These findings suggest that chemerin plays a role in endometriosis‐related pelvic inflammation.